Strategi Komunikasi Jakarta Coffee House Dalam Membangun Customer Engagement Melalui Media Sosial Dan Komunikasi Interpersonal - Irman Saleh; Muhamad Aqil Muzahid (Universitas Persada Indonesia YAI, 2026)
The development of the coffee shop industry in Indonesia is influenced not only by product quality but also by the effectiveness of communication strategies that can build long-term relationships with customers. Jakarta Coffee House is one of the coffee shops that develops a coffee education concept, interpersonal service, and the use of social media as a marketing communication tool. This study aims to analyze Jakarta Coffee House's communication strategies in building customer engagement. The research uses a descriptive qualitative method with data collection techniques including observation, in-depth interviews, documentation, and literature review. Analysis is carried out through data reduction, data presentation, and drawing conclusions using source triangulation. The results show that baristas' interpersonal communication, providing education about local coffee, social media activities, and organizing various community activities becomes a key factor in building an emotional connection with customers. That strategy not only boosts customer loyalty but also strengthens the image of Jakarta Coffee House as a space for communication and social interaction.